(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article examines the development of pilgrimage tourism in the Kingdom of Saudi Arabia, associated with the Hajj in the lunar month of Zulhijjah and the Umrah throughout the year. The main indicators of the world’s leading countries in international tourism and the countries of the Middle East are presented using statistical data. The place and role of the Kingdom in the global tourism industry are assessed. The conditions that prompted the Saudi leadership to diversify the economy by developing alternative types of tourism to reduce the country’s dependence on oil are revealed. The importance of implementing the large-scale project " Vision-2030 " is substantiated to attract more tourists from foreign countries, especially Western countries. A comparative analysis of trends in the development of pilgrimage and traditional tourism in the Kingdom of Saudi Arabia is made.